2001
DOI: 10.1046/j.1471-5740.2001.00003.x
|View full text |Cite
|
Sign up to set email alerts
|

The nutritional content of male prisoners' diet in the UK

Abstract: The Prison Catering Service has changed from a Ration Scale to a pre‐select menu system as the basis for providing prisoners' meals. The purpose of this research was to ascertain how this may have affected male prisoners' nutritional intake. Using a modified visual estimation technique, the dietary intake of 506 prisoners (mean age 35 years, height 1.77 m and weight 78.03 kg) in eight prisons was estimated for a 24‐h period. Results show that overall, the mean nutrient intake from food provided by HM Prisons (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
18
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(24 citation statements)
references
References 3 publications
4
18
2
Order By: Relevance
“…(2001) also found that the diet consumed by male prisoners compared favourably with the general population, with a result of 36.2% energy as fat. Carbohydrate intake (as percentage energy) was close to the recommended 50% and was comparable with the 50% found by Edwards et al . (2001).…”
Section: Discussionsupporting
confidence: 89%
See 4 more Smart Citations
“…(2001) also found that the diet consumed by male prisoners compared favourably with the general population, with a result of 36.2% energy as fat. Carbohydrate intake (as percentage energy) was close to the recommended 50% and was comparable with the 50% found by Edwards et al . (2001).…”
Section: Discussionsupporting
confidence: 89%
“…Average energy intake was close to the EAR, and compared well with data from Edwards et al . (2001), who found an average intake of 10.8 MJ across the eight prisons included in their study (Table 4).…”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations